Effects of Exercise Training on Hippocampus Concentrations of Insulin and IGF-1 in Diabetic Rats - Gomes, Ricardo Jose [UNESP]; Machado de Oliveira, Camila Aparecida [UNESP]; Ribeiro, Carla [UNESP]; de Alencar Mota, Clecia Soares [UNESP]; Moura, Leandro Pereira [UNESP]; Marcondes Cesar Tognoli, Lilian Mari [UNESP]; Curiacos de Almeida Leme, Jose Alexandre [UNESP]; Luciano, Eliete [UNESP]; Rostom de Mello, Maria Alice [UNESP] (Wiley-liss, 2009)
The present study investigated the role of swimming training on cerebral metabolism and hippocampus concentrations of insulin and IGF-1 in diabetic rats. Wistar rats were divided in sedentary control (SC), trained control (TC), sedentary diabetic (SD), and trained diabetic (TD). Diabetes was induced by Alloxan (35 mg kg(-1) b.w.). Training program consisted in swimming 5 days/week, 1 h/day, 8 weeks, supporting a load corresponding to 90% of maximal lactate steady state (MLSS). For MLSS determination, rats were submitted to three sessions of 25-min supporting loads of 4, 5, or 6% of body wt, with intervals of I week. Blood samples were collected every 5 min for lactate determination. An acute exercise test (25 min to 90% of MLSS) was done in 7th week to confirm the efficacy of training. All dependent variables were analyzed by one-way analysis of variance (ANOVA) and a significance level of P < 0.05 was used for all comparisons. The Bonferroni test was used for post hoc comparisons. At the end of the training period, rats were sacrificed and sample blood was collected for determinations of serum glucose, insulin, GH, and IGF-1. Samples of gastrocnemius muscle and liver were removed to evaluate glycogen content. Hippocampus was extracted to determinate glycogen, insulin, and IGF-1 contents. Diabetes decreased serum GH, IGF-1, and liver glycogen stores in SD. Diabetes also increased hippocampus glycogen and reduced hippocampus IGF-1 content. Physical training recovered liver and hippocampus glycogen stores and promoted increases in serum IGF-1 in TD group. Physical training restored hippocampus IGF-1 content in diabetic group. It was concluded that in diabetic rats, physical training induces important metabolic and hormonal alterations that are associated with an improvement in glucose homeostasis and with an increased activity in the systemic and hippocampus IGF-1 peptide. (C) 2009 Wiley-Liss, Inc.
Keywords: diabetes; insulin-like growth factor-1; brain and exercise training